Pioneering Dalit Resistance: A Study of Saint Visionaries - Kanchan, Kanan; Sharma, Vandana (Kalágatos, 2025)
It has been for centuries that the Indian society has been hierarchized on the lines of caste: videlicet, higher and lower castes. Since this division is by birth and perpetual, it needed to be interrogated and critiqued. Such investigation, implying need for awareness and resisting of atrocities was acutely felt from fifteenth century onwards. Saints and seers of the period began to articulate this assertion five centuries ago. It is in the writings of these poet-intellectuals that the earliest questioning of caste divisions and their alternative has been suggested. These poet-seers have stressed innate goodness of human nature and suggested the need for virtuous life that is utopic in its formulation. These voices gained strength and momentum over time and caste their spell on dalit communities. They have led dalit resistance by providing positive resolution to the baneful social divisions that have affected the lives of lower castes in all aspects. These pioneers of assertion of innate human dignity have been torchbearers for subsequent efforts by social reformers and gramscian organic intellectuals, who are trying to improve the lot of communities. Thus, it is imperative to closely study the writings of these socio-economic reformers, in order to understand the dalit scenario as also the dire need for ascension of the downtrodden in the Indian society.